Harmonisasi Hubungan Legislatif-Eksekutif Berdasarkan Undang-Undang No. 22 Tahun 1999 - Redjo, Samugyo Ibnu (Jurnal Civicus, 2002)
Harmonisasi Hubungan Legislatif-Eksekutif Berdasarkan Undang-Undang No. 22 Tahun 1999